The cellist of Sarajevo - Galloway, Steven, 1975- (New York : Riverhead Books, 2008)
A bread line in besieged Sarajevo. A mortar lobbed by Serb soldiers on the hill. Death for 22 people. A cellist sees it all and determines to honor the deadand perhaps assuage his own painby playing Albinoni's Adagio on the spot for 22 days. And so Galloway opens his first novel, inspired by true events, weaving together four lives to tell the awful story of Sarajevo's devastation. Aside from the cellist, there's Kenan, who risks his life every few days to carry plastic canisters to the brewery and retrieve water for his family. Dragan, who got his family out before the bombs started falling, works at the bakery for, literally, his daily bread. Both must cower on street corners and watch those who risk crossing get shot or killed. Arrow, who uses an alias, is a sniper desperate to defend her city and just as desperate not to compromise her humanity by hating the men who rain death down on the city. In the end, each takes a stand, small or large, to assure that the "Sarajevo that [they want] to live is alive again." Galloway writes simply and affectingly, occasionally resorting to cliché and just as often hitting a sweet, clear note that makes the siege of Sarajevo very real.
Keywords: Yugoslav War, 1991-1995 -- Fiction; Violoncellists -- Fiction; Snipers -- Fiction; Sarajevo (Bosnia and Hercegovina) -- Fiction; War fiction